Magnesium: does it reduce ischemia/reperfusion injury in an adnexal torsion rat model? - Celik Kavak E; Gulcu Bulmus F; Bulmus O; Kavak SB; Kocaman N (Dove Medical Press, 2018)
Ebru Celik Kavak,1 Funda Gulcu Bulmus,2 Ozgur Bulmus,3 Salih Burcin Kavak,1 Nevin Kocaman4 1Department of Obstetrics and Gynecology, 2Vocational School of Health Services, 3Department of Physiology, 4Department of Histology and Embryology, School of Medicine, Firat University, Elazig, Turkey Aim: The aim of the present study was to assess the protective effects of magnesium sulfate (MgSO4) on ischemia/reperfusion (I/R) induced ovarian damage in a rat ovarian torsion model.Methods: Forty-two female Sprague Dawley rats were included in the study. They were divided into six groups as Group 1, sham; Group 2, bilateral ovarian torsion; Group 3, bilateral ovarian torsion–detorsion; Group 4, MgSO4–sham; Group 5, MgSO4–bilateral ovarian torsion; Group 6, bilateral ovarian torsion–MgSO4–detorsion. Both torsion and detorsion periods lasted 3 hours. In Groups 4, 5 and 6, MgSO4 (600 mg/kg) was administered by intraperitoneal route 30 minutes before sham operation, torsion and detorsion, respectively. At the end of the study period, both ovaries were removed. One of the ovaries was used for histopathological analyses and the other for biochemical analyses.Results: In the torsion–detorsion group, all the histopathological scores were higher compared to the sham and torsion only group (p<0.05). Administration of MgSO4 only caused significant decrease in the inflammatory cell scores of the torsion–detorsion group (p<0.05). MgSO4, whether given before torsion or before detorsion, suppressed malondialdehyde levels when compared to the untreated groups (p<0.01 and p<0.001, respectively). Glutathione peroxidase activities were significantly higher in the MgSO4 applied torsion and detorsion groups than Groups 2 and 3 (p<0.05, for both). Administration of MgSO4 also caused an increase in glutathione levels in the torsion and detorsion groups compared to the torsion only and detorsion only groups (p<0.05, for both). Also, total oxidant status levels decreased in the MgSO4 applied torsion and detorsion groups compared to the untreated corresponding ones (p<0.01 and p<0.001, respectively). MgSO4 significantly decreased the Oxidative Stress Index levels in the torsion–detorsion group compared to Group 2 (p<0.001).Conclusion: Histopathological and biochemical analysis revealed that prophylactic treatment with MgSO4 reduces the changes observed in I/R injury in a rat model. Keywords: ovarian torsion, ischemia/reperfusion injury, magnesium sulfate